Irisin and betatrophin responses to 9 h of passive heat exposure: Influence of age, hypertension, and type 2 diabetes - Joel M. Garrett; James J. McCormick; Kelli E. King; Robert D. Meade; Pierre Boulay; Ronald J. Sigal; Fergus K. O'Connor; Glen P. Kenny (Physiological Reports, 2025)
Abstract Age‐ and disease‐related metabolic responses to prolonged passive heat exposure are poorly understood. We evaluated serum irisin and betatrophin responses to 9 h of passive heat exposure (40°C, 9% relative humidity) in 19 young adults (19–31 years) and 37 older adults (61–78 years), including those with hypertension (HTN) and type 2 diabetes (T2D). Serum concentrations of irisin and betatrophin were assessed at baseline and at the end of the passive heat exposure using enzyme‐linked immunosorbent assays. Generalized linear models were employed to examine changes over time and across subgroups, with fold‐change computed as exponentiated coefficients. Younger adults exhibited significantly higher baseline irisin (2.81‐fold, p = 0.003) and betatrophin (8.15‐fold, p < 0.001) levels compared to older adults. Betatrophin concentrations were further reduced in older adults with HTN (0.55‐fold, p = 0.02) and T2D (0.55‐fold, p = 0.047). Despite inducing physiological strain, 9 h of passive heat exposure did not alter circulating irisin or betatrophin concentrations in any group (p > 0.66). While passive heat exposure alone does not trigger metabolic hormone responses, lower baseline concentrations may indicate reduced cellular heat tolerance with aging. These findings highlight potential metabolic vulnerabilities in older and heat‐sensitive populations and build on previous findings in this series. ClinicalTrials.gov identifier: NCT04353076